Stone Pipe and Metal Container Design Semiotic Analysis of Sacral Objects - Újvári Edit (DISEGNO: A DESIGNKULTÚRA FOLYÓIRATA, 2022)
Design or the designer’s activity is not only designing an object, but also a complex mode of socialcultural relations and environmental situations. This paper focuses on the semiotic analysis of two historical examples where László Moholy-Nagy’s views ([1946] 1971)—which I interpret as “form adjusting itself to society”—are perfectly applicable. One object included in the design semiotic analysis is a Lakota ceremonial pipe, and the other is a sacral object of European Medieval culture, the Sainte-Foy reliquary of Conques. In both cases, the analysis is centred around formal and functional elements and materials that are impregnated with meaning. I intend to explain how, as sign vehicles (signifiers), the shape, ornamental elements, and materials of sacral objects, represent meanings and content. How is the form of these objects related to their function?